2010
DOI: 10.1111/j.1574-6941.2010.00890.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and localization of  the obligate endosymbiotic bacterium in the birch catkin bug Kleidocerys resedae (Heteroptera: Lygaeidae, Ischnorhynchinae)

Abstract: In contrast to specific bacterial symbionts of many stinkbugs, which are harboured extracellularly in the lumina of midgut sacs or tubular outgrowths, the obligate endosymbiont of birch catkin bug Kleidocerys resedae (Heteroptera: Lygaeidae) resides in a red-coloured, raspberry-shaped mycetome, localized abdominally, close to the midgut section. Phylogenetic analysis, based on the 16S rRNA gene and the groEL (chaperonin) gene, showed that the bacteria belong to the gamma-subdivision of the Proteobacteria and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 64 publications
3
39
0
Order By: Relevance
“…Unfortunately, no high-resolution phylogeny of Lygaeoidea bugs based on multilocus gene sequences which would elucidate the status of different lygaeoid (sub)families has been available to date. Nevertheless, on the basis of the differently structured bacteriomes as well as their phylogenetically distinct endosymbionts described here and in previous studies (15,27,28,32), we suggest that at least three major symbiotic systems have developed independently among these lygaeoid bugs: (i) the betaproteobacterial gut symbionts of the genus Burkholderia within crypts of the posterior midgut section in species of the Berytidae, Blissidae, Cymidae, Pachygronthidae, and Rhyparochromidae; (ii) the gammaproteobacterial endosymbionts "Ca. Kleidoceria schneideri" of Kleidocerys spp., "Ca.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Unfortunately, no high-resolution phylogeny of Lygaeoidea bugs based on multilocus gene sequences which would elucidate the status of different lygaeoid (sub)families has been available to date. Nevertheless, on the basis of the differently structured bacteriomes as well as their phylogenetically distinct endosymbionts described here and in previous studies (15,27,28,32), we suggest that at least three major symbiotic systems have developed independently among these lygaeoid bugs: (i) the betaproteobacterial gut symbionts of the genus Burkholderia within crypts of the posterior midgut section in species of the Berytidae, Blissidae, Cymidae, Pachygronthidae, and Rhyparochromidae; (ii) the gammaproteobacterial endosymbionts "Ca. Kleidoceria schneideri" of Kleidocerys spp., "Ca.…”
Section: Discussionsupporting
confidence: 63%
“…The eubacterial 16S rRNA gene was PCR amplified using the universal primers 07F (5=-AGAGTTTGATCMTGGCTCAG-3=) and 1507R (5=-TACCTTGTTA CGACTTCAC-3=) (30). A 1.65-kb segment of the bacterial groEL gene (which encodes the 60-kDa heat shock protein GroEL) was amplified with the primers Gro-F2 (5=-ATGGCAGCTAAAGAMGTAAAATTYGG-3=) and Gro-R2 (5=-TTACATCATRCCRCCCAT-3=) (27). The insect mitochondrial cytochrome oxidase I (COI) gene was amplified and sequenced with the primers mtD4_F (5=-TACAATTTATCGCCTAAACTTCAGCC-3=) and Nancy_R (5=-CCCGGTAAAATTAAA ATATAAACTTC-3=) (46).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive, histological investigations by Buchner (1965) and more recent ultrastructural studies (Cheng & Hou, 2001;Szklarzewicz & Moskal, 2001;Szklarzewicz et al, 2006Szklarzewicz et al, , 2010Szklarzewicz et al, , 2013Sacchi et al, 2008;Kuechler et al, 2010Kuechler et al, , 2011Matsuura et al, 2012;Swiatoniowska et al, 2013) have shown that during hemipteran evolution various modes of inheritance of endosymbiotic microorganisms by subsequent generations have developed. The extracellular gut bacteria that are typical of most the heteropterans so far examined (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While several atypical stinkbugs of the family Lygaeidae are associated with a primary endocellular bacterial symbiont in the bacteriome (39,40,41,43), the majority of stinkbugs are associated with a primary extracellular bacterial symbiont within specialized midgut portions called crypts or ceca (19, 24, 25, 28-30, 32-37, 51-53, 60). When experimentally deprived of the gut symbiont, these stinkbugs suffer retarded growth, sterility, and/or high mortality (1,19,24,27,33,35,37,51,60), indicating important biological roles of the symbiont for the host.…”
mentioning
confidence: 99%